2021
DOI: 10.3390/ma14237274
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Properties and Electron Scattering Mechanisms in a Nb Film with a Single Weak-Link Excavated by Focused Ion Beam

Abstract: Granularity is one of the main features restricting the maximum current which a superconductor can carry without losses, persisting as an important research topic when applications are concerned. To directly observe its effects on a typical thin superconducting specimen, we have modeled the simplest possible granular system by fabricating a single artificial weak-link in the center of a high-quality Nb film using the focused ion beam technique. Then, its microstructural, magnetic, and electric properties in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…From 92.6 to 48.0 Oe, the black profile decreases less and becomes increasingly similar to the red one, indicating that the flux pushed inward by the d-line movement is partially retained by the WL. This is related to an increased vortex pinning potential in the WL due to its reduced thickness and FIB-induced defects, which act as pinning centers and locally suppress T c [3,30]-see Appendix A. The observed relative increase in B corroborates the increase in m l across the WL seen in Fig.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…From 92.6 to 48.0 Oe, the black profile decreases less and becomes increasingly similar to the red one, indicating that the flux pushed inward by the d-line movement is partially retained by the WL. This is related to an increased vortex pinning potential in the WL due to its reduced thickness and FIB-induced defects, which act as pinning centers and locally suppress T c [3,30]-see Appendix A. The observed relative increase in B corroborates the increase in m l across the WL seen in Fig.…”
Section: Resultssupporting
confidence: 60%
“…Sample preparation details are given in Ref. [30]. Global dc magnetic responses are obtained in a Quantum Design MPMS-5S in the perpendicular geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 2(a)-2(d) were selected to highlight the difference among the thicker and the thinner regions of the specimen. The fact that we do not observe additional symmetrical d lines anywhere in the film [53,68] is a strong indication that there exists a smooth thickness gradient, as represented in Fig. 1(c).…”
Section: Resultsmentioning
confidence: 56%
“…In 1911, Heike Kamerlingh Onnes determined that when liquid helium was heated to -269ºC, the electrical resistance of the material was disappeared. Thus, superconductivity is a phenomenon first understood, approaching close to 4 degrees Celsius of absolute temperature in Kelvin [16]. Twenty-two years after this work, German researchers Walther Meissner and Robert Ochsenfeld, while studying the behavior of matter at extremely cold temperatures, found that a superconducting material affects the magnetic field [17][18][19].…”
Section: Introductionmentioning
confidence: 99%